On monoids of metric preserving functions - Bilet, Viktoriia; Dovgoshey, Oleksiy (Frontiers in Applied Mathematics and Statistics, 2024)
Let X be a class of metric spaces and let PX be the set of all f : [0, ∞) → [0, ∞) preserving X, i.e., (Y, f ∘ ρ) ∈ X whenever (Y, ρ) ∈ X. For arbitrary subset A of the set of all metric preserving functions, we show that the equality PX = A has a solution if A is a monoid with respect to the operation of function composition. In particular, for the set SI of all amenable subadditive increasing functions, there is a class X of metric spaces such that PX = SI holds. 2020 Mathematics Subject Classification Primary 26A30, Secondary 54E35, 20M20